Beneficial effects of reduced soft tissue vibrations with compression garments on delayed neuromuscular impairments induced by an exhaustive downhill run - Gassier, Robin; Espeit, Loïc; Ravel, Antoine; Beaudou, Pierre; Trama, Robin; Edouard, Pascal; Thouze, Arsène; Féasson, Léonard; Hintzy, Frédérique; Rossi, Jérémy; Hautier, Christophe (Frontiers in Sports and Active Living, 2025)
IntroductionSoft tissue vibrations (STV) have been extensively researched for their effects on muscle fatigue and damage, but their influence during running remains unclear. As compression garments are known to lower STV, they have shown benefits on acute neuromuscular responses to downhill running. However, an in-depth analysis of changes in STV has never been proposed, and previous protocols did not overcome the repeated bout effect. This study aims to investigate whether compression shorts could reduce STV parameters and related neuromuscular impairments using a unilateral compression protocol.Materials and methodsTwenty healthy men performed a downhill run until exhaustion while wearing shorts that compressed one thigh with the contralateral leg serving as a control. Foot–ground impacts (FGI), STV, and muscle activation of the Vastus Lateralis were measured on both legs while running using accelerometers to obtain FGI and STV, and surface electromyographic sensors (EMG) for muscle activation. Time–frequency analyses were applied to acceleration and EMG signals with statistical non-parametric mapping applied to the continuous data to assess time and compression effects. Neuromuscular parameters such as maximal voluntary contraction torque, voluntary activation, and torque evoked by 10 and 100 Hz doublet stimulation were assessed before, after, and 48 h post exercise, alongside perceived fatigue and muscle soreness. Mixed linear models and paired Student's t-tests were used to analyze neuromuscular outcomes.ResultsWhile results showed that both FGI and STV magnitude increased during the run by 19.7% (P = 0.002) and 17.8% (P = 0.003), respectively, compression reduced the magnitude and frequency of STV by 15.1% (P = 0.013) and 11.7% (P = 0.001), respectively, without influencing FGI or muscle activation. Although neuromuscular parameters were altered in both legs, losses of torque evoked by 10 and 100 Hz doublets were lower in the compressed leg 48 h post exercise (P < 0.001 and P = 0.001, respectively).ConclusionThis study revealed the potential of compression garments to act as a mechanical support that attenuates high-frequency STV during downhill running and mitigates subsequent delayed neuromuscular alterations.